PERAN TEKNOLOGI DALAM MENGATASI KRISIS PENDIDIKAN DI DAERAH TERPENCIL - Firdaus, Khairul; Ritonga, Mahyudin (STKIP Pesisir Selatan, 2024)
The education crisis in remote areas in Indonesia is one of the main challenges hampering equal distribution of education quality. This article examines the role of technology in overcoming various obstacles faced by the education sector in these regions. Education in remote areas, from elementary to senior level, really needs the right technology so that it can develop in line with today's times. Information and communications technology (ICT) offers innovative solutions to improve access and quality of education, through e-learning, educational applications and other digital tools. However, the application of technology in remote areas faces various obstacles, including limited infrastructure, uneven internet access, and low digital literacy among teachers and students. The research method uses literature studies from various valid reading sources. This article offers various solutions and initiatives and strategies that have been implemented to overcome this challenge, such as training programs for teachers, improving digital infrastructure, and collaboration between the government and the private sector. With a holistic and integrated approach, technology can be the key to overcoming the education crisis in remote areas and encouraging better educational equality throughout Indonesia.